Monday

April 21, 2014

April 21, 2014

Posted by **Please Help!** on Wednesday, June 13, 2012 at 12:56pm.

- Algebra 2 -
**Steve**, Wednesday, June 13, 2012 at 1:16pmlog

_{4}(x-2)(x+1) = 1

(x-2)(x+1) = 4

x^2 - x - 6 = 0

(x-3)(x+2)

x = 3 or -2

however, x = -2 does not fit the original equation, since log of negative numbers are not defined.

So, the only solution is x=3

**Related Questions**

Logarithms - Solve log4 x + log4(x-2)=log4(15) I know how do the example in my ...

Algebra 2 - Simplify: 1. 2log10^5+log10^4 2. 2log3^6-log3^4 3. log4^40-log4^5 4...

Algebra II - Solve, round to four decimal places if necessary: log4(x-9)=2 ...

Math - solve for x: log4 X - log4 2 = 2 log(2x) = 2 Now what do I do?

Math(Please check) - solve for x: log4 X - log4 2 = 2 log(2x) = 2 Now what do I ...

math - Solve the equation algebraically. Round the result to three decimal ...

Math - Evaluate the expression without using a calculator: log4(2)= ____? Use a ...

Math Algebra 2 - #4. Express the logarithm in terms of log2M and log2N: log2 1/...

Trig/Pre-Calc - Could someone please help me on this problem. I'm really ...

algebra II logarithms - f(x)=log4 (x)+3 how could i get this so i could graph it...